Nutritional value and degradability of oak wood roughage and its feeding effects on growth performance and behavior of Hanwoo steers during the early fattening period - Ye Ri Ju; Youl Chang Baek; Sun Sik Jang; Young Kyoon Oh; Sung Suk Lee; Yong Sik Kim; Keun Kyu Park (Asian-Australasian Journal of Animal Sciences, 2020)
Objective This study was conducted to evaluate changes in nutritional value and in situ dry matter (DM) degradability of oak and pine wood before and after steam-digestion process (60 min/160°C/6 atm) and feeding effect of the oak roughage on performance and behavior of Hanwoo steers. Methods Chemical composition and tannin concentration were analyzed for oak and pine trees before and after the pretreatment. In situ DM and effective degradability of these samples were assessed using a nylon bag method. In vivo trial was performed to estimate animal performance and behavior, using steers fed total mixed ration (TMR) diets containing 0% (control), 25% (OR-25), and 50% (OR-50) of the oak roughage. Eighteen steers were allocated into nine pens (2 steers/pen, 3 pens/treatment) for 52 days according to body weight (BW) and age. Results By the steam-digestion treatment, the neutral detergent-insoluble fiber was decreased from 86.5% to 71.5% for oak and from 92.4% to 80.5% for pine, thereby increasing non-fiber carbohydrate. In situ DM degradability of treated oak reached 38% at 72 h, whereas that of untreated oak was only 11.9%. The 0 h degradability of the treated pine increased from 5.9% to 12.1%, but the degradability was unchanged thereafter. Animal performance including BW, average daily gain, DM intake, and feed conversion ratio was not different among control and oak treatments. No differences were detected in animal behavior such as lying, standing, rumination, drinking, and eating, except walking. Walking was higher in control than oak treatments with numerically higher eating and lower lying times, probably due to bulkier characteristics of rice straw in the diet. Conclusion This study demonstrates that the oak roughage can be substituted for 50% of total forage or 100% of rice straw in TMR diets at early fattening stage of Hanwoo steers.